Addictions / Second Edition - Degenhardt Louisa; Hall Wayne; Proudfoot Heather; Teeson Maree (Psychology Press, Ltd, 2012)
This book incorporates advances in research and practice over the last ten years. Series Preface, Acknowledgements, The Nature of Addiction, Who Becomes Addicted?, The Health Consequences of Alcohol and Other Drug Use and Dependence, Theories of Addiction: Causes and Maintenance of Addiction, Alcohol, Nicotine, Cannabis, Opioids, Psychostimulants: Cocaine and Amphetamines and Ecstasy, Addiction: Looking Ahead, Further Reading, References, Author and Subject Index.